Unknown, Precarious, and Multifaceted: The Dismantling of Foreign Correspondent Work in News Agencies in Chile; [Desconocidos, Precarios y Multifacéticos: El Desmantelamiento del Trabajo de Corresponsal Extranjero en Agencias Noticiosas en Chile] - Faure-, A (Universidad Complutense Madrid, 2025)
International news agencies are undergoing a transformation in their business models, journalistic production processes, and the way they relate to their audiences and clients. The emergence of new, low-cost communication channels and the speed of social networks put pressure on these agencies’ key role in satisfying local markets and audiences. This article seeks to understand how international news agencies adapt to these new models and processes in Chile. Based on 16 semi-structured interviews with professionals from the most important agencies with offices in Chile (AP, Reuters, AFP, EFE, and Xinhua), the results of this article show an undermined professional status due to the casualization of correspondent work and even its dismantling, findings which are consistent with previous studies in other contexts. However, this article identifies local particularities of this work that navigate between the tensions of a political economy and professional roles in a scarcely studied journalistic culture, marked by the flexibilization and precariousness of working conditions. In this way, correspondents verbalize the dismantling of their status (unknown), their working conditions (precarious), and their professional boundaries (multifaceted). © 2025 Universidad Complutense Madrid. All rights reserved.